Inventory Accounting Methods: Factors Affecting Basis of The Choice - Rendy Aprianto Maha Putra; Anita Carolina (Master of Accounting Universitas Trunojoyo Madura, 2019)
This research aims to analyze the effects of company size, inventory variability, cost of goods sold variability, gross profit margin, leverage, current ratio, and managerial ownership in selecting the inventory accounting methods. The population of this research was manufacturing companies listed in the Indonesia Stock Exchange in 2015-2018. In addition, this research used a purposive sampling method to determine the sample. The research results indicate that company size and inventory variability affect the choice of inventory accounting methods, while variability of cost of goods sold, gross profit margin, leverage, current ratio, and managerial ownership do not affect the choice of inventory accounting methods.